Maternal Divinity, Fetishised Commodity - Adhora Ahmed (Spectrum)
Women’s bodies in postcolonial Indian society are interpreted and utilised to serve multiple systems of oppression, as examined in the work of writer Mahasweta Devi. Her short story “Breast-Giver” is about a professional wet-nurse named Jashoda, whose breasts and body are continually exploited until she succumbs to breast cancer. By engaging with several conceptual frameworks, including Marxist, subaltern, feminist, and psychoanalytic theories, I examine how the symbolism of Jashoda’s breasts changes throughout Devi’s story. In the first half of the story, Jashoda’s breasts are objectified in sexual and consumerist terms by her husband, while her body is perceived by her employers as a tool of labour. Since she produces a surplus of breast milk for her employers’ children and grandchildren, Jashoda’s exploitation is venerated through frequent comparisons to Hindu goddesses. In the second half of the story, Jashoda’s inability to lactate and her subsequent cancer completely invalidate her existence and reduce her to an expendable and discarded body, especially in the juxtaposition between her desirable breast milk and the abject pus from her cancer sores. Therefore, religious veneration and sexual attention awarded to Jashoda’s breasts are relevant only as long as they can be exploited to produce milk for the capitalist enterprise of her employers. Devi’s story thus uses the imagery of Jashoda’s breasts to conceptualise the effects of the intersecting oppressive systems of patriarchy and neoliberal capitalism on the subaltern woman in postcolonial Indian society.